Effects of COVID-19 during lockdown in Nepal - Mahato, Preeti; Tamang, Pasang; Shahi, Prakash; Aryal, Nirmal; Regmi, Pramod; van Teijlingen, Edwin; Simkhada, Padam (Europasian Journal of Medical Sciences, 2020)
Nepal started its full lockdown on March 24, 2020 and has been extended until 14 June 2020 as a precaution for prevention of COVID-19 infection. However, the strict lockdown has been criticised by many as not all the deaths are caused by COVID-19. The long and strict lockdown have had some negative effects in many aspects of health of an individual in the community. Many women are facing barriers to access maternity health care during the lockdown period and there has been rise in the suicidal behaviour such as sucidal attempt and actual suicide itself among the general population. As the lockdown began in Nepal, all the school and colleges were suspended, and children were forced to spend their time indoors and exams has been postponed leaving the students stressed about the uncertainty of their future. Social distancing, isolation and quarantine at home can result in isolated in an abusive home where there could be even more increase in abuse during such crisis. Millions of babies are missing the routine vaccinations which is a threat to global achievement in immunization. Apart from the rise in negative impact on health of Nepali people, there are other impacts related to health such as serious impacts on logistics and supply management including shortage of medicine and food supply; and impacts on farming including both production and sale. Nepal took several precautionary measures as a response towards COVID-19 such as First, limiting international air travel, sealing the land border-crossings with India and introduction of social distancing measures. However, with rise in deaths due to non COVID related causes and negative impacts on economic and financial condition of the country, there is a need for the country to ease its lockdown. Contact tracing, making face mask mandatory along with social distancing measure can be an alternative to lockdown for Nepal while the country is preparing to ease its lockdown. Social distancing, hygiene, lifestyle factors and PPE measures need to continue for long term, whilst we need to keep working on the big public health issues such as poverty reduction, improving access to health service to achieve universal health coverage.